Effect of Adding Porcelain and Glass Powder Mixture on Epoxy Properties - Ali Salih, Yaseen; Faeq Yass, Mohammed; Shihab Ahmed, Ahmed; I. Abdulla, Aziz (International Journal of Engineering and Technology, 2018)
In this research, porcelain powder and glass was added by 0.25% (0.15% porcelain powder and 0.1% glass powder) to the epoxy used in the concrete strengthening. The addition improved epoxy properties and reduced the cost. The results showed that the addition of porcelain and glass powder decrease the interaction temperature by 11.37%, epoxy flow by 10.41%, and increase the compressive strength by 7.61%. Upon testing the improved epoxy cubes under the effect of temperatures up to 200áµ’ C compression resistance decreased by 6.36%, while both modulus of rupture and modulus of elasticity improved by (1.03% and 4.11%) respectively. The epoxy was tested and used to strengthen reinforced concrete beams and tests showed good improvement in flexural properties.Â